Lignin-based microporous carbon nanofibers/S (LMCF@S) high performance cathode for superior room temperature Na–S batteries - Kiai, Maryam Sadat; Aslfattahi, Navid; Baydogan, Nilgun; Samylingam, Lingenthiran; Kadirgama, Kumaran; Kok, Chee Kuang (Elsevier, 2025)
Sodium-sulfur batteries (Na–S) present a compelling option for large-scale energy storage due to their significant storage capacity, coupled with the abundant and cost-effective nature of their constituent materials. However, their practical deployment is hindered by several critical issues, including the low conductivity of sulfur and its reduction products, volume expansion, the shuttling effect of polysulfides, and the formation of sodium dendrites, all of which can contribute to rapid capacity degradation. Herein, lignin-derived microporous carbon nanofibers/S (LMCF@S) were successfully produced by employing polyvinylpyrrolidone (PVP) and lignin as the precursor and zinc nitrate hexahydrate (ZNH) as an additive, combination of electrospinning, pre-oxidation, and carbonization techniques. The cell is assembled with LMCF@S cathode and Na foil anode, resulting in a remarkable capacity of 642 mAh g− 1 over 100 cycles at a current density of 1 A g− 1 . The high density of micropores in the LMCF@S cathode facilitates robust chemical bonding and rapid redox kinetics during the conversion reaction, resulting in enhanced utilization of sodium polysulfides (NaPSs) for the advancement of nextgeneration sodium-sulfur (Na–S) batteries.